2004
DOI: 10.1210/jc.2003-031158
|View full text |Cite
|
Sign up to set email alerts
|

Drospirenone for the Treatment of Hirsute Women with Polycystic Ovary Syndrome: A Clinical, Endocrinological, Metabolic Pilot Study

Abstract: The aim of this study was to investigate the effects of the new estro-progestinic containing the antimineralcorticoid progestogen drospirenone (DRSP) in women with polycystic ovary syndrome (PCOS). Fifteen hirsute PCOS patients were treated with 30 g ethinyl estradiol plus 3 mg DRSP for 12 cycles. Ultrasonographic pelvic exams, evaluation of hirsutism scores, and hormonal and lipid profile assays were performed at baseline and after three, six, and 12 cycles of treatment. An oral glucose tolerance test and eug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 36 publications
7
94
0
15
Order By: Relevance
“…This indicates that drospirenone-containing oral contraceptives may be more effective in the treatment of hyperandrogenism than oral contraceptives that use 17α-hydroxyprogesterone derivatives as the progestin agents. 69 A similar study conducted over 12 cycles confirmed the same results. 70 In addition, there is also evidence that treatment with EE30 + DRSP decreases the severity of acne in women with polycystic ovarian syndrome.…”
Section: Oral Contraceptives Containing Drospirenonesupporting
confidence: 64%
See 2 more Smart Citations
“…This indicates that drospirenone-containing oral contraceptives may be more effective in the treatment of hyperandrogenism than oral contraceptives that use 17α-hydroxyprogesterone derivatives as the progestin agents. 69 A similar study conducted over 12 cycles confirmed the same results. 70 In addition, there is also evidence that treatment with EE30 + DRSP decreases the severity of acne in women with polycystic ovarian syndrome.…”
Section: Oral Contraceptives Containing Drospirenonesupporting
confidence: 64%
“…In another study of women with polycystic ovarian syndrome, androstenedione, DHEAS, testosterone, and free testosterone levels were reduced when the women were treated with EE30 + DRSP. 69 The same study showed that the magnitude of the sex hormone-binding globulin increase found with EE30 + DRSP treatment was greater than that found with treatment using 17α-hydroxyprogesterone derivatives. This indicates that drospirenone-containing oral contraceptives may be more effective in the treatment of hyperandrogenism than oral contraceptives that use 17α-hydroxyprogesterone derivatives as the progestin agents.…”
Section: Oral Contraceptives Containing Drospirenonementioning
confidence: 92%
See 1 more Smart Citation
“…Oral contraceptives are used for the treatment of PCOS. Combined oral contraceptives containing drospirenone are preferred especially in the PCOS patients with hirsutism [8] . The risk of myocardial infarction and intracerebral events is 2.5% higher in the patients taking combined oral contraceptives containing low dose estrogen [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Drospirenone is normally found in combined oral contraceptives at a dose of 3 mg. In studies that evaluated the effects of ethinyl estradiol/drospirenone in women with PCOS, an improvement in menstrual cycles, hirsutism, and acne has been observed (38,39).…”
Section: Drospirenonementioning
confidence: 99%